2020
DOI: 10.1021/acs.langmuir.0c01613
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption of Myoglobin and Corona Formation on Silica Nanoparticles

Abstract: The adsorption of proteins from aqueous medium leads to the formation of protein corona on nanoparticles. The formation of protein corona is governed by a complex interplay of protein−particle and protein−protein interactions, such as electrostatics, van der Waals, hydrophobic, hydrogen bonding, and solvation. The experimental parameters influencing these interactions, and thus governing the protein corona formation on nanoparticles, are currently poorly understood. This lack of understanding is due to the com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(34 citation statements)
references
References 60 publications
2
32
0
Order By: Relevance
“…Considering this and the fact that the spike protein molecules are oriented with the top part exposed to the bulk solution one can deduce that the effective zeta potential of the virion should be positive, which can enhance its affinity to model surfaces used in experiments such as mica,[ 29 ] and to typical fomite surfaces, for example silica, cellulose fibers, etc. [ [30] , [31] , [32] , [33] ], which are often negatively charged. On the other hand, the middle and lower parts of the protein are negatively charged, which ensure its stabilization and prevents cluster formation, as shown experimentally in Ref.…”
Section: The Spike Proteinmentioning
confidence: 99%
“…Considering this and the fact that the spike protein molecules are oriented with the top part exposed to the bulk solution one can deduce that the effective zeta potential of the virion should be positive, which can enhance its affinity to model surfaces used in experiments such as mica,[ 29 ] and to typical fomite surfaces, for example silica, cellulose fibers, etc. [ [30] , [31] , [32] , [33] ], which are often negatively charged. On the other hand, the middle and lower parts of the protein are negatively charged, which ensure its stabilization and prevents cluster formation, as shown experimentally in Ref.…”
Section: The Spike Proteinmentioning
confidence: 99%
“…From all these data, it can be concluded that the conjugation efficiency of allergens with both candidate NPs is quite different. From previous reports, Alhydrogel ® adsorbs proteins dominantly through ligand exchange and by electrostatic interactions [ 29 ], whereas SiO 2 NPs adsorb proteins mainly by hydrophobic and electrostatic forces [ 30 , 31 ]. As both model allergens have a pI of around 5 (Bet v 1, 5.4; BM4, 5.6), they exhibit a negative net charge at pH 7.4 [ 32 ].…”
Section: Resultsmentioning
confidence: 99%
“…Dynamic light scattering (DLS) is a non-invasive technique that relates the mean particle size to the timescale of fluctuations in light scattered from the nanoparticles. In protein-binding experiments, the formation of a protein corona will lead to an increase in the apparent hydrodynamic diameter (D H ) of the nanoparticles (Piella et al, 2017;Lee et al, 2020;McClain et al, 2020). When GB3 or FBS proteins saturate the AuNP surface, the D H observed by DLS increases from 18.3 ± 0.4 nm (bare AuNP) to 24.3 ± 0.1 and 34.3 ± 0.4 nm, respectively (Figure 1B).…”
Section: The Challenges Of Studying Adsorption In Mixturesmentioning
confidence: 99%
“…Understanding this physiological response is predicated on the physical chemistry of proteinnanoparticle interactions, especially in the context of complex biological fluids. Multiple techniques exist to monitor thermodynamics and kinetics of binding for purified proteins on a uniform population of nanoparticles; however, this type of reductionist approach may not always work (Lacerda et al, 2010;Lee et al, 2020). Specifically, multiple studies have found that the binding affinity of an individual protein fails to predict its composition in the final protein corona formed in a mixture (Monopoli et al, 2011;Zhang et al, 2019).…”
Section: Introductionmentioning
confidence: 99%